Facial Hyperpigmentation Following Adalimumab - Salem, Mahjoubi Yasmine; Imen, Aouinti; Israa, Dahmani; Fatma, Zgolli; Ons, Charfi; Sihem, El Aidli (Current Drug Safety, 2025)
BackgroundTumor necrosis factor alpha (TNF-α) inhibitors, such as adalimumab, have significantly advanced the treatment of inflammatory diseases. However, these therapies are associated with various cutaneous adverse reactions.Case PresentationWe describe two rare instances of isolated facial hyperpigmentation induced by adalimumab. Both patients presented with asymptomatic, isolated brown macules on the cheeks following adalimumab treatment for ankylosing spondylitis. The hyperpigmentation appeared shortly after starting the medication in both cases. In one case, the hyperpigmentation persisted despite stopping the medication, while in the second case, it completely resolved within one month after discontinuation. However, in the second patient, the hyperpigmentation recurred after switching to certolizumab, another TNF-α inhibitor. No skin biopsies were performed, and both patients were otherwise healthy, with normal laboratory evaluations.ConclusionHyperpigmentation is an uncommon adverse reaction of this class of drugs, with only a few reported cases in the literature. The recurrence of hyperpigmentation after switching to another TNF-α agent, certolizumab, further suggests that this reaction may be a class effect, adding new insights into the spectrum of cutaneous side effects associated with TNF-α inhibitors. Clinicians should consider this potential side effect in patients presenting with hyperpigmentation, and sun protection should be recommended as a preventive measure.
Keywords: adverse effects